GAGASAN DAN KONSEP DASAR TEACHING GAMES FOR UNDERSTANDING ( TGfU) - Saryono Saryono (Jurnal Pendidikan Jasmani Indonesia, 2009)
This paper was inspired by the emergence of Teaching Games for Understanding (TGfU) as one of approaches in physical education learning founded by Bunker and Thorpe. TGfU needs to be developed in order to better school physical education. Better understanding and basic concept on the TGfU should be posessed by physical education teachers to ensure the appropriateness and the advantages in the practice. This article describes TGfU as a newly approach in physical education, basic concept, and various perspectives on TGfU. The explaination and presentation using various figures and table would help the readers to better understand about TGfU. This paper concludes that TGfU is an innovation towards a better physical education learning. Kata kunci: gagasan, konsep dasar, Teaching Games for Understanding (TGfU)